A contribution to the use of numerical modelling for the characterisation of climatic variables aimed at identifying instability thresholds in clay slopes. Issue 3 (18th August 2018) - Pedone, G.; Ruggieri, G.; Trizzino, R.
Abstract : The paper reports the results of a slope-atmosphere interaction analysis performed with reference to geo-hydro-mechanical conditions typically observed on the Southern Apennines (Italy). The aim of the analysis is to gain some understanding in the characterisation of climatic variables which can be employed to identify instability thresholds in clay slopes. A finite element seepage analysis has been undertaken first, showing that Mediterranean climates can produce significant pore pressure changes also at depths which are not usually considered to be affected by atmospheric conditions. Making use of the pore pressure distributions obtained from the seepage analysis, limit equilibrium analyses have been carried out for a 5m and a 20m deep landslide body, confirming that also deep movements in clay slopes can be related to slope-atmosphere interaction. The characterisation of climatic variables aimed at identifying instability thresholds is finally discussed on the basis of the analyses reported in the paper. The results show that net rainfall cumulated over 2 and 6 months represent suitable threshold climatic variables for the 5m and the 20m deep landslide body respectively. These findings suggest that the stability of a clay slope, when referred to shallow landslide movements, is likely to depend on the rainfall infiltrating over a few weeks at least, rather than on the occurrence of extreme and isolated events. On the other hand, when deep movements are considered, the stability is more likely to depend on the amount of rainfall gradually infiltrating during the most rainy seasons.